The ABC of communism. A popular explanation of the program of the Communist Party of Russia. New introd. by S. Heitman. [Transl. from the Russian by (M.) E. and C. Paul] (The University of Michigan Press, 1966)
With index. Ann Arbor Paperbacks for the study of Communism and Marxism, AA 112, 2 A.